2011
DOI: 10.1111/j.1600-0714.2011.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trials for the treatment of burning mouth syndrome: an evidence‐based review of the literature

Abstract: Burning mouth syndrome (BMS) is defined as a chronic pain condition, characterized symptomatically by a generalized or localized burning sensation in the oral cavity. Various drugs have been used in attempting to treat BMS, but there is insufficient evidence to show the effect of any effective treatment. The aim of this review was to assess the effectiveness of therapies for BMS. Randomized controlled trials (RCTs) enrolling patients with a diagnosis of BMS were identified by searching Pubmed and Scoppus datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 25 publications
2
46
0
1
Order By: Relevance
“…On the other hand, professional contact and welcoming also show positive result in light of the patient emotional component. This correlations were reported in the literature 16,24 , and considering the primary BMS subtypes 9 and that the neuropathic pain may be associated to BMS may be a mixture of peripheric or central 26 , the proposed ideal therapy must be individual 27 . However, new studies are needed in order to define better treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, professional contact and welcoming also show positive result in light of the patient emotional component. This correlations were reported in the literature 16,24 , and considering the primary BMS subtypes 9 and that the neuropathic pain may be associated to BMS may be a mixture of peripheric or central 26 , the proposed ideal therapy must be individual 27 . However, new studies are needed in order to define better treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to minimize the adverse effects, the use of topical clonazepan was evaluated, with reduction of 70% in the burning sensation 15 . However, the study performed by Moraes et al 16 observed that even in topical form, some patients reported side effects, such as drowsiness, xerostomia, and increased burning sensation in the mouth in some cases.…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, the binding of capsaicin inactivates the neuronal responses to heat. 58 Prolonged exposure to capsaicin has been shown to deplete TRPV1 in peripheral tissues, thus contributing to the long-term desensitization of nociceptors and a reduction in the burning sensation. 58 Then, activation of TRPV1 can induce persistent depolarization of the nerve terminals, causing a decrease in their ability to generate and propagate action potentials.…”
Section: Capsaicinmentioning
confidence: 99%
“…58 Prolonged exposure to capsaicin has been shown to deplete TRPV1 in peripheral tissues, thus contributing to the long-term desensitization of nociceptors and a reduction in the burning sensation. 58 Then, activation of TRPV1 can induce persistent depolarization of the nerve terminals, causing a decrease in their ability to generate and propagate action potentials. 57,59 In addition, expression of TRPV1 in various brain regions has been established, and capsaicin results in an increase in the excitatory glutamatergic synaptic transmission in the nucleus tractus solitarius, locus coeruleus, dopaminergic neurons of the substantia nigra, and the preoptic hypothalamic neurons.…”
Section: Capsaicinmentioning
confidence: 99%
See 1 more Smart Citation